Relationship between multiple water swallows and gastroesophageal reflux in patients with normal esophageal motility. Issue 6 (1st September 2015) - Choi, Y. J.; Park, M. I.; Park, S. J.; Moon, W.; Kim, S. E.; Yoo, C. H.; Kwon, H. J.
Summary: Multiple water swallows (MWS) stimulates neural inhibition, resulting in abolition of contractions in the esophageal body and complete lower esophageal sphincter relaxation, which is followed by peristalsis and the lower esophageal sphincter contraction. We assessed the relationship between MWS and gastroesophageal reflux in patients with esophageal symptoms and with normal findings by high-resolution manometry (HRM). We retrospectively reviewed the clinical records of patients who underwent HRM and a 24-hour ambulatory impedance-pH study. Correlation between the findings of the impedance-pH study and abnormal MWS responses without motility disorders was evaluated. Independent t -tests were used for statistical analysis. Of 28 patients, 20 (71%) had abnormal MWS responses: four (20%) had abnormal responses during MWS, six (30%) had abnormal responses after MWS, and 10 (50%) had abnormal responses both during and after MWS. Total acid exposure times were significantly longer in patients with abnormal MWS responses than in patients with normal MWS responses. In particular, upright acid exposure time and all reflux percent times were significantly longer in patients with abnormal MWS responses. However, bolus clearance time and longest reflux episode were not different between the two groups. Abnormal MWS responses predicted increased acid exposure times in patients with normal findings of HRM by the Chicago classification.